2022
DOI: 10.7717/peerj.13594
|View full text |Cite
|
Sign up to set email alerts
|

Machine-learning based prediction and analysis of prognostic risk factors in patients with candidemia and bacteraemia: a 5-year analysis

Abstract: Bacteraemia has attracted great attention owing to its serious outcomes, including deterioration of the primary disease, infection, severe sepsis, overwhelming septic shock or even death. Candidemia, secondary to bacteraemia, is frequently seen in hospitalised patients, especially in those with weak immune systems, and may lead to lethal outcomes and a poor prognosis. Moreover, higher morbidity and mortality associated with candidemia. Owing to the complexity of patient conditions, the occurrence of candidemia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 64 publications
(63 reference statements)
0
5
0
Order By: Relevance
“…Overall mortality was observed in 73% of the patients. 18 31.1% of our patients had a poor outcome, and 6(6.7%) patients had HIV. HIV was also related to poor outcomes in our study participants.…”
Section: Discussionmentioning
confidence: 65%
“…Overall mortality was observed in 73% of the patients. 18 31.1% of our patients had a poor outcome, and 6(6.7%) patients had HIV. HIV was also related to poor outcomes in our study participants.…”
Section: Discussionmentioning
confidence: 65%
“…According to the anticandida susceptibility test, candida strains isolated from 243 patients were not resistant to amphotericin B, which was consistent with another study on anticandida susceptibility of candida. 17,18 Although fluconazole is the most commonly used anticandida drug, our results show that 7.4% (18/243) of candida are resistant to fluconazole, which is the drug with the strongest resistance. This is similar to the results of a recent study on candida resistance.…”
Section: Discussionmentioning
confidence: 69%
“…The presented model was developed using readily available data. Unlike previous studies and prognostic models [ 12 , 13 , 14 , 20 , 21 ], all parameters reflect patient demographics (i.e., age and gender) and recent medical history data. It shares some parameters with the healthcare-associated infection definition [ 15 ] by adding information about the need of central lines and any recent invasive procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies evaluated prognostic factors in more selected clusters of patients: a machine-learning-based study showed that the most important predictors of death in patients with concomitant candidemia and bacteriaemia are age, serum creatinine level, leukocyte and lymphocyte counts, total bilirubin level, procalcitonin level, endotoxic shock, length of stay in the intensive care unit (ICU), length of stay in the hospital and total parental nutrition [ 13 ]; another recent Chinese cohort study indicates that ICU admission, coronary heart disease, biliary infection and the use of tigecycline are independent prognostic factors of 90-day mortality in elderly people (≥65 years old) with both typical (e.g., transplant recipient, hematological malignancy) and atypical (e.g., diabetes mellitus, liver cirrhosis, burns, postoperative) immunosuppression status, and that a decrease in body mass index is a protective factor [ 14 ].…”
Section: Introductionmentioning
confidence: 99%